Editorial Cartoon Visual Metaphor in Jakarta Newspapers at 1950-1957 - Sunarto, Priyanto (TAWARIKH, 2012)
ABSTRACT: The purpose of this historical study is to investigate the relationship among visual metaphor in editorial cartoon with political and cultural situations at the Parliamentary Democracy period in Indonesia (1950-1959). As a new nation-state, Indonesia had just begun to experiment with democracy. The multi-party parliamentary system with symmetrical power sharing had triggered severe competition among political parties which tried to bring down each other. This feud was clearly and openly written in polemics found in many newspapers in Jakarta at that time. In such an atmosphere could observe the role of editorial cartoon be easily. This political openness could, then, stimulate a rich variety of visual metaphorical patterns and editorial cartoon emotive attitudes. This research is using qualitative method, analyzing artefacts by surfing the cultural network encapsulating them. This study presents empirical evidence showing a strong relationship between the editorial cartoons and the political side the media is taking, along with the political and cultural situations which support them. A political symmetric situation gives a free opportunity to the editorial cartoon to express metaphor with an open emotive attitude. KEY WORDS: Newspaper, Parliamentary Democracy period in Indonesia, editorial cartoon, visual metaphor, meaning, and emotive aspect.About the Author: Dr. Ir. Priyanto Sunarto is a Senior Lecturer at the Faculty of Art and Design ITB (Bandung Institute of Technology), Jalan Ganesha No. 10 Tamansari, Bandung, West Java, Indonesia. He can be reached at: fleur2ria@yahoo.comHow to cite this article? Sunarto, Priyanto. (2012). âEditorial Cartoon Visual Metaphor in Jakarta Newspapers at 1950-1957â in TAWARIKH: International Journal for Historical Studies, Vol.3(2) April, pp.211-234. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 19, 2012); Revised (March 22, 2012); and Published (April 28, 2012).